Generation of a Reconfigurable Logical Cell Using Evolutionary Computation - Campos Cantón, I.; Torres Treviño, Luis Martín; Campos Cantón, E.; Femat, Ricardo (2013)
Adaptation in nature is a relevant research area that has many applications in artificial systems, which can be used for the benefit of society. Particularly in biology, a neuron can reconfigure itself to develop different tasks using the same structure; however, this procedure is a mystery. The processes of adaptation, learning, and coupling between them have been research pursuits therein, and the understanding of this processes can help to build artificial devices.The act of joining living tissue with electronics has long been imagined in the world of science fiction, but cybernetic organisms are now one step closer to reality, thanks to work emerging from researchers that have built tiny electronic meshes out of silicon nanowires and have used them as scaffolds to grow nerve, heart, and muscle tissue